Site specific design response spectrum proposed for the capital city of Agartala, Tripura. Issue 5 (2nd September 2016) - Sil, Arjun; Sitharam, TG
ABSTRACT: The design response spectrum is smooth in shape compared to other response spectra. The objective of design spectra is to estimate the possible earthquake lateral loads which may experience on a particular structure during its design life. In this study, an attempt has been made to develop, design response spectra for the Agartala city, Tripura which is one of the North Eastern states in India considered at the highest level of seismic activity in the country having a zone factor 0.36g as per Indian seismic code (BIS 1893-2002). Based on the present data set collected from 1731-2011, the region is characterized and the seismicity parameters estimated separately for each source zone by Gutenberg and Richter (G-R) relationship. The two ground motion models were used for the hazard prediction. However, hazard curve, and uniform hazard response spectra (UHRS) (2% and 10% probability level for 50 years) has been developed for the Agartala at seismic bedrock level condition. Further, the NEHRP (National Earthquake Hazards Reduction Program) site classes D and E-types have been identified based on the average shear wave velocity at an upper 30 m depth of the subsurface soil profile. The direct shear wave velocity profiles were obtained through multi channel analysis of surface wave tests conducted at 27 locations at Agartala city. The design response spectra have been developed at the surface level for both the site classes. The results could be used as direct inputs for earthquake resistant design of civil engineering infrastructures of the study area.